Hubungan Kadar Hemoglobin Dengan Kemampuan Kognitif Pada Remaja di Sukoharjo Jawa Tengah - Ardityawati, Alviani Suci, Dr. Dr. M. Shoim Dasuki, M.Kes (2017)
Teenagers are a national asset for future development. The distribution of cognitive performance is still below average in 25% of all countries, and one known cause of low cognitive performance is low hemoglobin levels. A low hemoglobin level may cause fatigue, lower studying concentration and lower academic performance. To determine correlation of between hemoglobin levels and cognitive performance in teenager students at Sukoharjo, Central Java. This research is an analytical observational study with a cross-sectional approach, in which sampling were conducted using Cluster Sampling. Results of Chi-Square analysis revealed a p value of 0,015. Conclusion presence of correlation between hemoglobin levels and cognitive performance in teenager students of SMP Muhammadiyah 1 Kartasura. Key word : Hemoglobin levels, Cognitive performance, Teenagers.